Variation and variability in Fusarium oxysporum f. sp. cumini causing wilt of cumin - Choudhary, Sanju; Godika, Shailesh (Indian Journal of Plant Protection, 2020)
Wilt of cumin incited by Fusarium oxysporum f. sp. cumini is one of the important disease and a big constraint in successful cultivation. Therefore, in the present study, 7 isolates of Fusarium oxysporum f. sp. cumini collected from different cumin growing areas of Rajasthan were assessed for cultural variations. To know the cultural variability in pathogen isolates they were grown on different nutritional media. All the isolates produced maximum mycelial growth on Czapek Dox Agar medium and the mycelial growth ranged from 7.1 cm (I3) to 9.0 cm (I1) followed by Potato Dextrose Agar media for mycelial growth where isolates I3 exhibited better growth. The data on dry fungal biomass of different isolates on broth media revealed that mean dry fungal biomass of all the seven isolates was highest (246.53 mg) on Czapek Dox medium followed by Potato Dextrose (231.92 mg) medium. Almost all the isolates produced highest dry fungal biomass on Czapek Dox medium except isolate I7 which showed highest dry fungal biomass on Potato Dextrose medium. In general, the Potato Dextrose and Czapek Dox broth media were found excellent for macro- and micro-conidia formation. Different grain media were evaluated for their effect on growth and sporulation (Macro- and micro-conidia formation) of fungal isolates. All the isolates showed fastest mean growth on chickpea medium followed by moong bean and maize where entire surface of substrate was covered in short period of 9.14, 10.00 and 10.14 days, respectively.